STUDY OF COORDINATION OF IMMUNOACTIVE PEPTIDES WITH METAL IONS AS A BASIS FOR THE DEVELOPMENT OF INNOVATIVE DRUGS - N. D. Bunyatyan; G. M. Bobiev (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The results of development of the immunomodulator timotsin based on coordination compounds dipeptide isoleucyl-tryptophan with zinc, including the synthesis of low molecular weight peptides by immunoactive activated esters, determination regarding the immunostimulatory activity of thymosin α1, study of coordination of dipeptide isoleucyltryptophan with zinc, study the immunostimulatory activity of coordination compounds, the results of preclinical and clinical studies of timotsin. pH-metric method and red-ox titration showed that the interaction of zinc and of dipeptide isoleucyl-tryptophan formed in solution following complex forms: [ZnHL] (lgæ = 3,71), Zn(HL)2 (lgβ = 0,279), ZnL(HL) (lgβ = 6,6), Zn2(HL)2 (lgβ = 188), Zn(OH)(HL) (lgβ = -0,256). It was shown that the immunostimulatory activity of coordination compounds is in 2-8 times greater than the starting dipeptide.The developed immunomodulatory drug timotsin showed high therapeutic efficacy in the treatment of viral hepatitis, malignant tumors of different localization, psoriasis and neurodermatitis. Timotsin is registered in Tajikistan (registration number of medical drug№000085T), Kyrgyzstan (medical drug №7137) and Turkmenistan (registration number 006371).